Extracción de quitina del cefalotórax del camarón litopenaeus vannamei utilizando método químico - Cando Centeno, Maryury Alexandra (2012)
The cephalothorax of the shrimp is a byproduct economically profitable, since it has high quality protein, pigments such as astaxanthin, chitin and its derivative quitosan. Las shrimp processing plants are big generators of these wastes, which can be considered important when there are alternatives bioconversion processes, they can be obtained by chemically defined compounds that have applications in chemical and food industry. Have waste valuable components such as chitin, which otherwise would be exploited and environmental contaminants that are susceptible to rapid decomposition orgánicascil substances degradation. These wastes are usually placed or discharged into coastal waters, abandoned land or in landfills, affecting self-purification capacity of water and the environment.  What is chitin? It is the most abundant organic substance in nature after cellulose, and perhaps the least known. Biopolymer is a polysaccharide derived from cellulose, in which the hydroxyl group of carbon 2 has been replaced by the acetamide group and whose monomer is 2-acetamido-2-deoxy-β-D-glucose forms a white substance, hard, inelastic, semi-transparent horny, insoluble in water and most solvents that have many uses in the medical, industrial, textile, agriculture and food. The objective of this research was to extract chitin from shrimp shrimp carapace, using the chemical method which consists mainly of three steps: deproteinization of shrimp heads with sodium hydroxide at moderate temperature, followed by demineralization with hydrochloric acid and finally lipid removal or bleaching with sodium hypochlorite. The result of this investigation was entirely satisfactory to reaffirm the use of the cephalothorax of shrimp in obtaining chitin. To carry out the isolation process, we implemented a controlled chemical treatment that consists of different stages, starting from a raw material composed of the cephalothorax washed and liquefied. Following the chemical method could be obtained chitin, reaching extract 3% - 4 % of chitin based on 2270 g of shrimp carapace. The deproteinization process involves treating the shells of crustaceans with a dilute aqueous solution of NaOH to dissolve the protein, at this stage should be borne in mind that treatments for long or very high temperatures can cause rupture of the chains and the partial deacetylation of the polymer. Demineralization in HCl is used at room temperature, which eliminates the main inorganic component of the shells of crustaceans is CaCO3. The process of bleaching or whitening is to remove the pigments in crustaceans such as astaxanthin, cantaxaxtina the astaceno, lutein and β-carotene using traditional oxidants such as NaOCl.